Assignment Methods in Online Learning with Cognitive Learning Outcomes Materials of the Golden Age of Islam - Ratu Suntiah; Maslani Maslani; Resa Umami (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
This study aims to find out students' responses to the assignment method relates to their cognitive learning outcomes in PAI subjects heyday of Islam class XI 1SMA Plus Damar Bangsa. This study uses a quantitative approach and descriptive method with data collection techniques through observation, tests, questionnaires, and interviews. And in this research, the data analysis is descriptive analysis and correlation analysis. From the results of the study, it was obtained: 1) The reality of student responses to the assignment method in online learning was in the sufficient category, based on an average result of 3.49 which was at intervals of 2.5-3.5. 2) The reality of students' cognitive learning outcomes in PAI subjects is in the sufficient category, based on an average value of 68.96 which is in the 60-69 interval. 3) The reality of students' responses to the assignment method in online learning has a relationship with students' cognitive learning outcomes which are in the sufficient category because they are in the interval 0.40-0.70. The results of the hypothesis test prove that t count = 2.93 > t table 2.04, then H0 is rejected and H1 is accepted. Thus, the hypothesis proposed is accepted, namely that there is a relationship between the assignment method in online learning and their cognitive learning outcomes in PAI subjects heyday of Islam in class XI 1 SMA Plus Damar Bangsa Kabupaten Sukabumi. Penelitian ini bertujuan untuk mengetahui tanggapan siswa terhadap metode penugasan hubungannya dengan hasil belajar kognitif PAI materi Masa Kejayaan Islam kelas XI 1 SMA Plus Damar Bangsa. Penelitian ini menggunakan pendekatan kuantitatif dan metode deskriptif dengan teknik pengumpulan data melalui observasi, tes, angket, dan wawancara. Dan dalam penelitian ini analisis datanya yaitu analisis deskriptif dan analisis korelasi. Dari hasil penelitian diperoleh: 1) Realitas tanggapan siswa terhadap metode penugasan dalam pembelajaran daring berkategori cukup, berdasarkan hasil rata-rata sebesar 3.49 yang berada pada interval 2.5-3.5. 2) Realitas hasil belajar kognitif PAI materi Masa Kejayaan Islam berkategori cukup, berdasarkan nilai rata-rata sebesar 68.96 yang berada pada interval 60-69. 3) Realitas tanggapan siswa terhadap metode penugasan dalam pembelajaran daring hubungannya dengan hasil belajar kognitif PAI materi Masa Kejayaan Islam termasuk kategori cukup karena berada pada interval 0.40-0.70. Hasil uji hipotesis membuktikan bahwa t hitung= 2.93 > t tabel 2.04 maka H0 Ditolak dan H1 diterima. Dengan demikian, hipotesis yang diajukan diterima yaitu terdapat hubungan antara metode penugasan dalam pembelajaran daring dengan hasil belajar kognitif PAI materi Masa Kejayaan Islam di kelas XI 1 SMA Plus Damar Bangsa Kab. Sukabumi.